Berichten. (Leuven : HIV-Integratiecentrum, 1992)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks ; vanaf 3(1993) zomer : tweemaandelijks
Redactie : C. Meunierstraat 95/8, 3000 Leuven
Nederlands
Periodiek